Optical Remote Sensing Fiber Bragg Device for Load Measurement - Patimapornchai, C.; Jewpraditkul, W.; Yupapin, P.P. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
This work is feasibility study of the load sensors, using optical remote measurement scheme. The optical head is fiber Bragg grating. The light source from He-Ne Laser is launched into the fiber coupler that is divided 2 parts: the first is transmitted to the sensing. The other part isn’t use. The return signal is connected to detector. A coherent light beam from a laser He-Ne with wavelength of 632.8 nm. It’s launched into fiber coupler and the end is connected to a sensing unit i.e. fiber Bragg grating. The return signal from applied load is detected by a detector and seen on the oscilloscope monitor. The change in output signal intensity relating to the applied loads is measured. The measurement relationship between the applied loads and output light intensity are detected where the long length of single mode fiber is shown the remote sensing sense. This advantage is use in the dangerous place of human, to develop to small load sensing, is remote sensing. Keywords: optical sensor, remote sensor Corresponding author: E-mail: cast@kmitl.ac.th